1993
DOI: 10.1177/00220345930720120701
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Dental Caries in the Primary Teeth of Children who Suffered from Infant Malnutrition

Abstract: A prospective, four-year longitudinal study of 209 Peruvian children was conducted to evaluate the effect of a single malnutrition episode occurring at infancy (i.e., < 1 year of age) on dental caries in the primary teeth. Children were recruited into the study at age 6-11 months after they had suffered from a malnutrition episode and were thus classified by anthropometry as either: (1) Normal; (2) Wasted (low weight for height); (3) Stunted (low height for age); or (4) Stunted and Wasted (S and W). Eruption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0
26

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 17 publications
4
45
0
26
Order By: Relevance
“…While several clinical studies have reported a positive correlation between malnutrition and caries in primary teeth (Alvarez & Navia, 1989; Ismail, 1998; Johansson, Saellström, Rajan, & Parameswaran, 1992), there is currently a limited understanding as to whether the same relationship exists for the permanent dentition. A review article published in 2005 (Psoter, Reid, & Katz, 2005) only identified one longitudinal case study from Peru (Alvarez et al, 1993), where a link between early childhood protein‐energy malnutrition (PEM) and caries in the permanent dentition was observed. This particular study argued that the same factors observed in experimental rat studies, where malnourishment due to PEM and Vitamin A deficiency resulted in impaired amelogenesis and reduced salivary flow rates, caused an increase in caries frequencies (Harris & Navia, 1980; Johansson, Ericson, Bowen, & Cole, 1985; Navia, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…While several clinical studies have reported a positive correlation between malnutrition and caries in primary teeth (Alvarez & Navia, 1989; Ismail, 1998; Johansson, Saellström, Rajan, & Parameswaran, 1992), there is currently a limited understanding as to whether the same relationship exists for the permanent dentition. A review article published in 2005 (Psoter, Reid, & Katz, 2005) only identified one longitudinal case study from Peru (Alvarez et al, 1993), where a link between early childhood protein‐energy malnutrition (PEM) and caries in the permanent dentition was observed. This particular study argued that the same factors observed in experimental rat studies, where malnourishment due to PEM and Vitamin A deficiency resulted in impaired amelogenesis and reduced salivary flow rates, caused an increase in caries frequencies (Harris & Navia, 1980; Johansson, Ericson, Bowen, & Cole, 1985; Navia, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…For age group 6 years, the prevalence of dental caries was low in underweight children (76.7% versus 87.8%). The possible explanation could be a delayed tooth eruption among malnourished children which may have resulted in delayed caries development 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Sendo relevante ressaltar que não apenas a ingestão inadequada de nutrientes, mas também as doenças infecciosas, contribuem para a instalação dos déficits nutricionais, devido à possibilidade de estas exporem a criança a repetidos eventos patológicos, capazes de levar à perda de peso e à morbidade de conseqüências significativas, dentro de um ciclo de repetição 28 . Deficiências nutricionais são capazes de repercutir no desenvolvimento de estruturas do organismo, entre as quais, os elementos dentais -tanto em seu processo de formação, quanto na sua cronologia de erupção 8 situação justificada pelos desequilíbrios nutricionais observados, e corroborada por estudos anteriores 10,30 .…”
Section: Discussionunclassified